Propuesta de intervención urbana en el barrio central de la parroquia Shell-Pastaza - Rodríguez Rodríguez, Jimmy Marcelo (2026)
The present research aims to generate an intervention to improve the urban and architectural public space in the existing urban voids in the Central neighborhood, belonging to Shell - Pastaza parish. To achieve this goal, clear objectives are set: first, to find and gather useful information that helps to understand the problems and the current situation of the Parish and the neighborhood as such, through the investigation of theoretical material and institutional documents. Subsequently, a detailed urban analysis of the sector will be conducted, aimed at detecting urban gaps and understanding their impact on the neighborhood’s layout. Based on this analysis, a comprehensive diagnosis will be developed to specifically address the identified issues. Finally, a functional and context-adapted urban-architectural intervention will be proposed, which addresses the needs of the inhabitants and contributes to improving the structure and quality of the urban space.